Guest

In one of your article about displacement of fringes, can you explain in a simple way about the formula P = S2P - [S1P+ µt - t] = S2P - S1P - (µ - 1)t = y.d/D - (µ - 1) ? nth fringe is shifted by ?y = D(µ-1)t/d = w/? (µ-1)t , because i need this for my university entrance exam. Thank you

In one of your article about displacement of fringes, can you explain in a simple way about the formula
P = S2P - [S1P+ µt - t] = S2P - S1P - (µ - 1)t = y.d/D - (µ - 1)
? nth fringe is shifted by ?y = D(µ-1)t/d = w/? (µ-1)t

, because i need this for my university entrance exam. Thank you

Grade:12

0 Answers

No Answer Yet!